Morphological variability of Trifolium repens L. (Fabaceae) - Lluga-Rizani, Kimete; Šoljan, Dubravka; Berisha, Naim; Kurteshi, Kemajl; Letaj, Kasum (Hacquetia, 2021)
The subject of our research was L. The aim was to assess the level of morphological and anatomical variability among populations from different habitats (meadows, roadsides, subalpine slopes) and different altitudes (891–1881 m) in Brezovica (Sharri Mountain, Kosovo). The investigation covered 26 morphological and anatomical traits in populations from 12 locations. From the results obtained during this research, it can be concluded that there is a significant difference among populations for most micro- and macro-morphological traits. There is also a tendency towards a reduction of most of the average values of the investigated parameters (total plant height, total leaf length, leaf petiole length, peduncle length, fruit weight, number of flowers in an inflorescence, stomata length on the upper leaf surface, and diameter of collateral bundle) in relation to altitude increase. However, trichome length showed consistency and was not affected by habitat and altitude changes. The results also lead to a proposal for taxonomic revision of this taxon.